Intrinsic dorsoventral patterning and extrinsic EGFR signaling genes control glial cell development in the Drosophila nervous system. - Kim, H.J.; Ahn, H.J.; Lee, S.; Kim, J.H.; Park, J.; Jeon, S.H.; Kim, S.H. (Neuroscience, 2015)
Dorsoventral patterning and epidermal growth factor receptor (EGFR) signaling genes are essential for determining neural identity and differentiation of the Drosophila nervous system. Their role in glial cell development in the Drosophila nervous system is not clearly established. Our study demonstrated that the dorsoventral patterning genes, vnd, ind, and msh, are intrinsically essential for the proper expression of a master glial cell regulator, gcm, and a differentiation gene, repo, in the lateral glia. In addition, we showed that esg is particularly required for their expression in the peripheral glia. These results indicate that the dorsoventral patterning and EGFR signaling genes are essential for identity determination and differentiation of the lateral glia by regulating proper expression of gcm and repo in the lateral glia from the early glial development. In contrast, overexpression of vnd, msh, spi, and Egfr genes repressed the expression of Repo in the ventral neuroectoderm, indicating that maintenance of correct columnar identity along the dorsoventral axis by proper expression of these genes is essential for restrictive formation of glial precursor cells in the lateral neuroectoderm. Therefore, the dorsoventral patterning and EGFR signaling genes play essential roles in correct identity determination and differentiation of lateral glia in the Drosophila nervous system.